Iklim Komunikasi dan Partisipasi dalam Program Pertanian Perkotaan - Nizzatul Amaliyah; Sarwititi Sarwoprasodjo (Institut Pertanian Bogor, 2018)
Urban farming programs are considered capable of overcoming problems in the city such as food availability. Urban farming activities can be successful if people participate. This study aims to analyze the relationship of individual characteristics with participation level in urban agriculture program, analyzing climate communication relationship of KWT Dahlia Indah and KWT Nusa Indah Lestari with participation level, and to analyze the relationship of participation level in the success of urban farming program in KWT Dahlia Indah and KWT Nusa Indah Lestari. The method used in this study is a quantitative method with a questionnaire instrument and supported by qualitative data with in-depth interviews of informants and respondents using question guides. The results of this study indicate that individual characteristics are not related to the level of participation. The existing communication climate in KWT is supportive and related to the level of participation. While the level of participation has a significant relationship with the success rate of urban farming program.